Performance Evaluation of the M-QAM Enhanced Subcarrier Index Modulation in the Multipath Fading Channel with the Non-Linear Amplifier - Si Sar Mi; Aphitchaya Siriwanitpong; Pornpawit Boonsrimuang; Pisit Boonsrimuang (My University, 2023)
One of the specifications of the next-generation mobile communication is to reduce the power consumption to transmit the signal. Enhanced subcarrier index modulation (eSIM-OFDM) is a novel multicarrier modulation scheme. However, the eSIM-OFDM scheme degraded a little frequency utilization than the conventional orthogonal frequency division multiplexing (C-OFDM) scheme at the higher M-QAM modulation techniques. It has a special feature to transmit the signal when compared with the C-OFDM scheme. Its special feature increased the power efficiency and improved the bit error rate (BER) performance than the C-OFDM scheme. In the literature, the BER performance of the eSIM-OFDM scheme is analyzed in the additive white Gaussian noise (AWGN) channel and compared BER performance of the C-OFDM scheme. But in the literature, the BER performance of the eSIM-OFDM scheme and C-OFDM scheme were not evaluated in the multipath fading channel. Because eSIM-OFDM includes a special feature called inactive and active subcarriers. In this paper, we will evaluate the BER performance of higher order modulated eSIM-OFDM signal in the multipath Rician fading channel by using the Zadoff-Chu sequence pilot in the non-linear mobile communication system and will compare the BER performance with the C-OFDM scheme. From the simulation results, we can see that the BER performance of the eSIM-OFDM scheme is much better than the C-OFDM scheme in the multipath Rician fading non-linear channel. In this paper, computer simulation will evaluate the BER performance of the higher order modulated eSIM-OFDM scheme in the multipath Rician fading non-linear channel.
Keywords: Advanced Wireless Communication Technologies; Cooperative Communication and Network Coding; Advanced Wireless Communication Techniques